Supermarkets and agricultural labor demand in Kenya: A gendered perspective - Rao, E.J.O.; Qaim, M. (Elsevier, 2013)
Many developing countries are experiencing a rapid expansion of supermarkets. New supermarket procurement systems could affect farming patterns and wider rural development. While previous studies have analyzed farm productivity and income effects, possible employment effects have received much less attention. Special supermarket requirements may entail intensified farm production and post-harvest handling, thus potentially increasing demand for hired labor. This could also have important gender implications, because female and male workers are often hired for distinct farm operations. Building on data from a recent survey of vegetable farmers in Kenya, a double-hurdle model of hired labor use is developed and estimated. Farmer participation in supermarket channels increases the likelihood of hiring labor by 20%, and demand for hired labor by 61%. A gender disaggregation shows that positive employment effects are especially pronounced for female laborers, who often belong to the most vulnerable population groups. Rural employment generation can be an important vehicle for poverty reduction.